Empowering youth organizations to revitalize Kampung Dolanan and enhance community well-being post-COVID-19 - Ariq Fikria Niagasi; Rafli Aditya Kristianto; Sierly Fransiska; Oktavia Damayanti; Rahma Inka Yovani; Siti Zidzuna Ilma Tiyana (Community Empowerment, 2024)
Established in 2015, Dolanan Village thrived until the COVID-19 pandemic forced its closure. However, the village also faced resident complaints due to mismanagement and lack of resources. To address these challenges, a community service program was implemented to strengthen Dolanan Village's institutional framework and equip residents with digital marketing skills. Through training in content creation, financial management, human resources, and digital marketing, residents gained the ability to develop activity budgets, establish standard operating procedures, and create marketing content using available resources. This program empowered the community and paves the way for a more sustainable and prosperous Dolanan Village.